2010
DOI: 10.3959/2009-10.1
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Gender Bias in Citation Rates of Publications by Dendrochronologists: What is Unique about this Discipline?

Abstract: Most academic disciplines have a gender bias that exists in the recognition of research publications: women's publications are cited at lower rates than men's publications. In this paper, we examined whether a similar gender bias existed for publications by dendrochronologists. Tree-ring research is a fairly small field where males outnumber females, and therefore the sample size was limited to 20 female dendrochronologists and 20 male dendrochronologists. It was determined that native language (English or non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 35 publications
1
22
0
2
Order By: Relevance
“…In geography and forestry, we found no existence of gender bias in citation rates (Table 1), a pattern that has also been identified in other science and social science disciplines (Lewison 2001;Penas and Willett 2006;Ledin et al 2007). This has been explained by frequent co-authorship among male and female authors, improved equality between the male and female researchers in the workplace, and because the authorship gender may not be known or considered when citing other's research (Xie and Shauman 1998;Copenheaver et al 2010). Geographers had significantly lower citation rates than foresters (Table 1).…”
Section: Author's Influence On Citation Ratementioning
confidence: 85%
See 3 more Smart Citations
“…In geography and forestry, we found no existence of gender bias in citation rates (Table 1), a pattern that has also been identified in other science and social science disciplines (Lewison 2001;Penas and Willett 2006;Ledin et al 2007). This has been explained by frequent co-authorship among male and female authors, improved equality between the male and female researchers in the workplace, and because the authorship gender may not be known or considered when citing other's research (Xie and Shauman 1998;Copenheaver et al 2010). Geographers had significantly lower citation rates than foresters (Table 1).…”
Section: Author's Influence On Citation Ratementioning
confidence: 85%
“…In male-dominated disciplines, papers authored by male researchers are cited more frequently than papers authored by females; possibly because female researchers experience more difficultly becoming fully integrated into the male-dominated research network (Stack 2002;Penas and Willett 2006). The third documented pattern is a lack of difference in citation rates between publications authored by males and females (Lewison 2001;Ledin et al 2007;Copenheaver et al 2010). This seems to be particularly common in fields where co-authorship frequently includes both sexes (Copenheaver et al 2010).…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…Some of these studies have also evaluated the impact of publications, through the number of citations or the journal impact factor. The literature in this area has shown mixed results, including no differences in the citation patterns of male and female academics (Cole and Zuckerman 1984;Lewison 2001;Ledin et al 2007;Mauleón et al 2008;Copenheaver et al 2010), a higher number of citations for female-authored papers (Long 1992;Symonds et al 2006;Borrego et al 2010), and fewer citations of papers authored by women (Hunter and Leahey 2010;Larivière et al 2011Larivière et al , 2013a. Recently, the global, cross-disciplinary bibliometric study undertaken by Larivière et al (2013a, b) showed that papers with female authors in key positions (sole authorship, first-and last-authorship) are cited less than those with males in key positions.…”
Section: Introductionmentioning
confidence: 99%